Application of the microRNA‐302/367 cluster in cancer therapy. Issue 4 (13th February 2020) - Liu, Jiajia; Wang, Ying; Ji, Ping; Jin, Xin
Abstract: As a novel class of noncoding RNAs, microRNAs (miRNAs) can effectively silence their target genes at the posttranscriptional level. Various biological processes, such as cell proliferation, differentiation, and motility, are regulated by miRNAs. In different diseases and different stages of disease, miRNAs have various expression patterns, which makes them candidate prognostic markers and therapeutic targets. Abnormal miRNA expression has been detected in numerous neoplastic diseases in humans, which indicates the potential role of miRNAs in tumorigenesis. Previous studies have indicated that miRNAs are involved in nearly the entire process of tumor development. MicroRNA‐302a, miR‐302b, miR‐302c, miR‐302d, and miR‐367 are members of the miR‐302/367 cluster that plays various biological roles in diverse neoplastic diseases by targeting different genes. These miRNAs have been implicated in several unique characteristics of cancer, including the evasion of growth suppressors, the sustained activation of proliferative signaling, the evasion of cell death and senescence, and the regulation of angiogenesis, invasion, and metastasis. This review provides a critical overview of miR‐302/367 cluster dysregulation and the subsequent effects in cancer and highlights the vast potential of members of this cluster as therapeutic targets and novel biomarkers. Abstract : The microRNA (miR)‐302/367 cluster has been implicated in several peculiarities of cancer including evading growth suppressors, sustaining proliferative signaling, and evading cell death and senescence, angiogenesis, invasion and metastasis. This review provides a critical overview of miR‐302/367 cluster dysregulation and the subsequent effects in cancer and demonstrates the indispensable roles of this cluster as therapeutic targets and novel biomarkers at current state researches.